Abstract 17984: No Longer Silent: A Synonymous Coding SNP Modifying a Novel MicroRNA-24: SCN5A Interaction Associates With Non-Arrhythmic Death in Heart Failure - Boudreau, Ryan L; Spengler, Ryan M; Skeie, Jessica M; Zhang, Xiaoming; Cheng, Congsheng; Yoon, Jin-Young; Gutmann, Rebecca A; Bloom, Heather L; Dudley, Samuel C; Ellinor, Patrick T; Shalaby, Alaa A; Weiss, Raul; et al. (Circulation (New York, N.Y.), 2015)
Mutations that disrupt the coding sequence of Nav1.5, the cardiac Na+ channel encoded by SCN5A, cause inherited arrhythmias and cardiomyopathy. Changes in Nav1.5 splice isoforms, localization and function have also been associated with prognosis in acquired heart disease. However, the role of genetic variants in SCN5A gene regulatory sequences (e.g. those modulating expression) remains poorly understood. MicroRNAs (miRs) have emerged as vital gene regulators in heart, having roles in cardiogenesis, contractile function, and disease. These small non-coding RNAs are loaded into Argonaute proteins to direct post-transcriptional gene suppression by base-pairing with target transcripts, and genetic variants altering miR binding sequences may influence disease. Here, we used high-throughput biochemical means (HITS-CLIP) to generate the first transcriptome-wide map of miR binding events in human heart (4000 sites across >2200 genes). Our query of the data uncovered >500 common SNPs residing in or nearby miR target sites. Among these, we identified a synonymous SNP (rs1805126, T/C) which alters a conserved miR-24 binding site in the terminal coding exon of SCN5A. We hypothesized that this SNP affects Nav1.5 expression and contributes to clinical outcomes in heart failure. In vitro experiments showed that miR-24 suppresses Na+ current on patch clamp analysis (~5-fold; p<0.001) and potently inhibits Nav1.5 expression, with rs1805126 allele C showing a greater decrease relative to T (66% vs. 52%, p<0.01). To assess the clinical relevance of this, we genotyped >1800 subjects with EFs≤30% and implantable cardioverter defibrillators (ICDs) from GRADE, a prospective multicenter study of genetic modulators of heart failure outcomes. We found that CC homozygotes had worse survival rates than T-allele carriers (HR=1.5, p=0.001), but no change in appropriate ICD shocks, a surrogate for sudden death. Together, these data reveal a novel miR-24:SCN5A:SNP regulatory axis that points to a surprising link between cardiac Na+ channel levels and non-arrhythmic death in heart failure. Overall, this work represents a key advance in exploring the interface of cardiac miRs with genetics and disease, perhaps signifying a broader functional relevance for “silent” SNPs.